Thermoplastic, thermally conductive nuclear radiation shielding composite material and method of making and use thereof
Patent Information
- Application Number
- CN202410665529.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-27
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-05-27
AI Technical Summary
在核反应堆内部的辐射热等恶劣环境作用下,聚乙烯基屏蔽材料导热率低,容易产生热量积聚;热变形温度低,在高温环境下容易发生蠕变失效,且综合屏蔽性能差,存在核泄漏等严重的安全隐患
[0049]本发明提供了一种热塑性导热核辐射屏蔽复合材料,该复合材料在低填料添加量下,取得了优异的导热性能,克服了聚合物导热性能普遍较差(一般小于1W/mK)的问题,可在高温辐射环境下使用;同时,本发明复合材料密度低、力学性能优异、对中子核辐射有良好的屏蔽效果,可作为高导热核辐射屏蔽复合材料使用,本发明制备得到的复合材料在核辐射防护领域中具有广阔的应用前景。
Smart Images

Figure CN118546451B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of functional composite materials technology, specifically relating to a thermoplastic thermally conductive nuclear radiation shielding composite material, its preparation method, and its applications. Background Technology
[0002] With increasing human demand for energy and growing concern for the environment, new energy sources are developing rapidly. Nuclear energy, as a clean and efficient energy form, has received widespread attention. However, while utilizing nuclear energy, nuclear reactors produce highly radioactive alpha, beta, and gamma rays. These rays have high energy and strong penetrating power, posing significant harm to human health and the environment. Therefore, nuclear radiation shielding materials are needed to shield these radioactive substances. Traditional nuclear radiation shielding materials include concrete and lead, but these materials suffer from problems such as heavy weight, large volume, poor portability, and limited application locations.
[0003] Due to the numerous problems with traditional nuclear radiation shielding materials, polymer-based shielding materials have attracted attention. According to the laws of conservation of momentum and energy, in order to transfer most of the neutron's energy through neutron scattering from the target nucleus, the mass of the target nucleus should be approximately equal to the mass of the neutron. Polyethylene (PE), containing a large number of hydrogen atoms, is often used as the polymer matrix for neutron shielding because the mass of the hydrogen atoms meets the above criteria, and the hydrogen nuclei can effectively scatter neutrons. However, polyethylene has poor thermomechanical properties, a low heat distortion temperature, and a low thermal conductivity. During use, polyethylene-based composite materials easily accumulate heat, leading to creep or melting failure, making them unsuitable for use as structural components. Therefore, it is necessary to improve its thermal conductivity so that it can quickly conduct heat to the environment during use, preventing heat accumulation and mitigating creep or structural damage caused by localized high temperatures. Detailed research on polyethylene-based shielding materials has already been conducted in relevant literature. For example, the literature "Study on shielding performance and mechanical properties of high-density polyethylene / lead boron composite material" (Shi Yong, Chen Bao, Zhang Long, et al. China Plastics, 2020, 34(1):51-57.) discloses the study on the shielding performance and mechanical properties of B4C modified HDPE composite material. The simulation results show that the thermal neutron shielding and gamma-ray shielding performance of the material has been improved. The literature "Simple approach to developing high-efficiency neutron shielding composites" (ZHANG X, ZHANG X, GUO S. Polymer Engineering & Science, 2019.) discloses the preparation of a multilayer HDPE / BN shielding composite material. They found that the more layers of the shielding material, the better the shielding performance. The literature "Designing a boron nitride polyethylene composite for shielding neutrons" (VIRA AD, MONE EM, RYAN EA, et al. APL Materials, 2023, 11(10):101-104.) discusses the structural optimization design of HDPE / BN shielding composite material to improve the shielding performance. Existing research largely focuses on the shielding performance of polyethylene composite materials, neglecting the urgent need for efficient heat dissipation of shielding materials in practical applications. Nuclear reactors and their piping loops are constantly exposed to high temperatures, high humidity, and high radiation. Under the harsh environment of radiant heat within nuclear reactors, polyethylene-based shielding materials exhibit low thermal conductivity, easily leading to heat accumulation; their low heat distortion temperature makes them prone to creep failure at high temperatures, and their overall shielding performance is poor, posing serious safety hazards such as nuclear leakage. Therefore, there is an urgent need to develop a new generation of low-density, easily processed, high thermal conductivity polymer-based nuclear radiation shielding composite materials. Summary of the Invention
[0004] The purpose of this invention is to provide a thermoplastic thermally conductive nuclear radiation shielding composite material, its preparation method, and its applications.
[0005] This invention provides a thermoplastic thermally conductive nuclear radiation shielding composite material, which is prepared from the following raw materials in the indicated mass percentages: 5-90% polyethylene or modified polyethylene, 0-90% ceramic matrix filler, 0-50% thermally conductive carbon matrix filler, and 5-90% shielding filler.
[0006] Furthermore, the aforementioned thermoplastic thermally conductive nuclear radiation shielding composite material is prepared from the following raw materials in the indicated mass percentages: 30-60% polyethylene or modified polyethylene, 10-30% ceramic matrix filler, 10-20% thermally conductive carbon matrix filler, and 20% shielding filler.
[0007] Alternatively, it is prepared from the following raw materials by weight percentage: 15-20% polyethylene or modified polyethylene, 0-5% ceramic-based filler, 0-5% thermally conductive carbon-based filler, and 80% shielding filler.
[0008] Furthermore, the aforementioned thermoplastic thermally conductive nuclear radiation shielding composite material is prepared from the following raw materials in the indicated mass percentages: 30-50% polyethylene or modified polyethylene, 10-30% ceramic matrix filler, 10-20% thermally conductive carbon matrix filler, and 20% shielding filler.
[0009] Alternatively, it is prepared from the following raw materials by weight percentage: 15% polyethylene or modified polyethylene, 0-5% ceramic-based filler, 0-5% thermally conductive carbon-based filler, and 80% shielding filler.
[0010] Furthermore, the aforementioned thermoplastic thermally conductive nuclear radiation shielding composite material is prepared from the following raw materials in the indicated mass percentages: 30-40% polyethylene or modified polyethylene, 20-30% ceramic matrix filler, 10-20% thermally conductive carbon matrix filler, and 20% shielding filler.
[0011] Furthermore, the aforementioned thermoplastic thermally conductive nuclear radiation shielding composite material is prepared from the following raw materials in the indicated mass percentages: 40% polyethylene or modified polyethylene, 20% ceramic matrix filler, 20% thermally conductive carbon matrix filler, and 20% shielding filler.
[0012] Alternatively, it is prepared from the following raw materials in the following mass percentages: 40% polyethylene or modified polyethylene, 30% ceramic-based filler, 10% thermally conductive carbon-based filler, and 20% shielding filler;
[0013] Alternatively, it is made from the following raw materials in the following mass percentages: 30% polyethylene or modified polyethylene, 30% ceramic-based filler, 20% thermally conductive carbon-based filler, and 20% shielding filler;
[0014] Alternatively, it is prepared from the following raw materials by weight percentage: 15% polyethylene or modified polyethylene, 5% ceramic-based filler, 0% thermally conductive carbon-based filler, and 80% shielding filler.
[0015] Furthermore,
[0016] The polyethylene is ultra-high molecular weight polyethylene;
[0017] And / or, the ceramic-based filler is boron nitride, B4C, aluminum nitride, aluminum oxide, zinc oxide, magnesium oxide, or silicon carbide;
[0018] And / or, the thermally conductive carbon-based filler is graphite, carbon fiber, carbon nanotube, graphene, or carbon black;
[0019] And / or, the shielding filler is lead, lead oxide, tungsten, tungsten monoboride, tungsten diboride, cadmium, iron, aluminum, or titanium.
[0020] Furthermore,
[0021] The polyethylene is ultra-high molecular weight polyethylene;
[0022] And / or, the ceramic-based filler is boron nitride;
[0023] And / or, the thermally conductive carbon-based filler is graphite;
[0024] And / or, the shielding filler is lead.
[0025] Furthermore, the molecular weight of the ultra-high molecular weight polyethylene is 2 million to 4 million.
[0026] The present invention also provides a method for preparing the aforementioned thermoplastic thermally conductive nuclear radiation shielding composite material, which includes the following steps:
[0027] The raw materials are weighed according to their mass percentages and prepared by hot pressing, extrusion molding or injection molding.
[0028] Preferably, the method for preparing the aforementioned thermoplastic thermally conductive nuclear radiation shielding composite material of the present invention includes the following steps:
[0029] (1) Set the mixing temperature to 180-220℃ and the rotation speed to 40-80 r / min;
[0030] (2) Add raw material polyethylene or modified polyethylene, thermally conductive carbon-based filler, ceramic-based filler and shielding filler in sequence;
[0031] (3) After all the raw materials are added, the mixture is stirred to obtain the material;
[0032] (4) Set the temperature of the upper and lower plates of the hot press to 180-200℃ and plasticize the material obtained in step (3);
[0033] (5) After purging the gas, maintain the pressure;
[0034] (6) Finally, cold press the product in a cold press to fix it, and you will get the product.
[0035] More preferably,
[0036] In step (2), the time for adding polyethylene and thermally conductive carbon-based filler is 5 to 10 minutes;
[0037] And / or, in step (3), the mixing time is 10 to 20 minutes;
[0038] And / or, in step (4), the plasticizing time is 5 to 10 minutes;
[0039] And / or, in step (5), the method of removing the gas is to repeatedly pressurize and depressurize to exhaust the gas 5 to 15 times;
[0040] And / or, in step (5), the holding temperature is 180-200°C, the pressure is 10-15 MPa, and the time is 10-20 min;
[0041] And / or, in step (6), the pressure of the cold pressing is 10-15 MPa and the time is 5-10 min.
[0042] More preferably,
[0043] In step (1), the mixing temperature is 200℃ and the rotation speed is 60r / min;
[0044] And / or, in step (4), the temperature of the hot-pressed upper and lower plates is 200°C;
[0045] And / or, in step (5), the pressure applied is 10-15 MPa, and the pressure released is 0 MPa.
[0046] The present invention also provides the use of the aforementioned thermoplastic thermally conductive nuclear radiation shielding composite material in the preparation of nuclear radiation shielding materials.
[0047] Furthermore, the nuclear radiation shielding material is a high thermal conductivity nuclear radiation shielding material used in high-temperature, nuclear power plant, and mobile nuclear equipment nuclear radiation environments.
[0048] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0049] This invention provides a thermoplastic thermally conductive nuclear radiation shielding composite material. This composite material achieves excellent thermal conductivity with low filler content, overcoming the problem of generally poor thermal conductivity of polymers (typically less than 1 W / mK), and can be used in high-temperature radiation environments. At the same time, the composite material of this invention has low density, excellent mechanical properties, and good shielding effect against neutron nuclear radiation, and can be used as a high thermal conductivity nuclear radiation shielding composite material. The composite material prepared by this invention has broad application prospects in the field of nuclear radiation protection.
[0050] This invention addresses the need for high thermal conductivity and lightweight shielding composite materials in the field of nuclear radiation shielding. By synergistically combining different functional filler particles with a relatively low filler particle content, it achieves simultaneous improvement in the thermal conductivity, mechanical strength, and shielding performance of UHMWPE-based composite materials, thereby meeting the application requirements of high thermal conductivity polymer-based shielding composite materials in the field of nuclear radiation protection.
[0051] Obviously, based on the above description of the present invention, and according to common technical knowledge and conventional methods in the field, various other modifications, substitutions or alterations can be made without departing from the basic technical concept of the present invention.
[0052] The following detailed embodiments further illustrate the above-described content of the present invention. However, this should not be construed as limiting the scope of the present invention to the following examples. All technologies implemented based on the above-described content of the present invention fall within the scope of the present invention. Attached Figure Description
[0053] Figure 1 The thermal conductivity and mechanical properties of pure UHMWPE and samples BN30C10, BN30C20, BN30C10Pb20 and BN30C20Pb20 prepared in Example 1 are as follows: (a) thermal conductivity; (b) contribution of filler per unit mass to thermal conductivity; (c) tensile strength; (d) flexural strength.
[0054] Figure 2 The images show SEM images of samples BN30C10Pb20 and BN30C20Pb20 prepared in Example 1. The first row shows the SEM image of sample BN30C10Pb20, and the second row shows the SEM image of sample BN30C20Pb20. The left image is magnified 43 times, the middle image is magnified 500 times, and the right image is magnified 1500 times.
[0055] Figure 3 The image shows the XRD pattern of the packing material.
[0056] Figure 4 This is a schematic diagram of the XRD analysis of the sample.
[0057] Figure 5 The XRD patterns of the A and B sides of samples BN30C10Pb20 and BN30C20Pb20 prepared in Example 1 are shown.
[0058] Figure 6 The results of thermal conductivity and mechanical property analysis for pure UHMWPE and the sample prepared in Example 2 are as follows: (a) thermal conductivity; (b) contribution of filler per unit mass to thermal conductivity; (c) tensile strength; (d) flexural strength.
[0059] Figure 7 The results of thermal conductivity and mechanical property analysis for pure UHMWPE and the sample prepared in Example 3 are as follows: (a) thermal conductivity; (b) contribution of filler per unit mass to thermal conductivity; (c) tensile strength; (d) flexural strength.
[0060] Figure 8 The images are SEM images of sample BN20C20Pb20 prepared in Example 2, and samples Pb80, Pb80C5, and Pb80BN5 prepared in Example 3. The top image in each column has a magnification of 40x, the middle image has a magnification of 500x, and the bottom image has a magnification of 1500x.
[0061] Figure 9 Mapping analysis of sample BN20C20Pb20 prepared in Example 2 and sample Pb80BN5 prepared in Example 3.
[0062] Figure 10 Geant4 simulation shielding results: (a), (b), and (c) show the neutron transmittance (I / I0), linear attenuation coefficient (μ), and mass attenuation coefficient (μ) of UHMWPE, BN10C10Pb20, BN20C10Pb20, and BN30C10Pb20, respectively. m Simulation results; (d), (e), and (f) represent the neutron transmittance (I / I0), linear attenuation coefficient (μ), and mass attenuation coefficient (μ) of BN10C20Pb20, BN20C20Pb20, and BN30C20Pb20, respectively. m Simulation results; (g), (h), and (i) represent the neutron transmittance (I / I0), linear attenuation coefficient (μ), and mass attenuation coefficient (μ) of Pb80, Pb80BN5, and Pb80C5, respectively. m Simulation results. Detailed Implementation
[0063] The raw materials and equipment used in the specific embodiments of the present invention are all known products, obtained by purchasing commercially available products.
[0064] 1. Experimental materials
[0065] Ultra-high molecular weight polyethylene (UHMWPE), brand name: L3000, Mitsui Chemicals, molecular weight around 3 million.
[0066] Hexagonal boron nitride (BN), in flake form with a particle size of 30 μm, was purchased from Dandong Rijin Technology Co., Ltd.
[0067] Lead powder (Pb) was purchased from Jinzhou Haixin Metal Materials Co., Ltd., with a particle size of 30-50μm.
[0068] Graphite powder (C), Qingdao Huatai Lubrication and Sealing Technology Co., Ltd., size 100 mesh.
[0069] 2. Experimental apparatus
[0070] Table 1. Experimental Apparatus
[0071]
[0072] Example 1: Preparation of the thermally conductive nuclear radiation shielding composite material of the present invention
[0073] The raw material formulation of the thermally conductive nuclear radiation shielding composite material of the present invention is shown in Table 2.
[0074] Table 2. Raw material formulation of the thermally conductive nuclear radiation shielding composite material of the present invention
[0075]
[0076] The preparation method of the UHMWPE-based thermally conductive nuclear radiation shielding composite material of this invention consists of two processes: mixing and hot pressing. The composite material is obtained by first mixing and then hot pressing. The specific preparation method is as follows:
[0077] 1. The mixing process is as follows:
[0078] (1) Start the internal mixer, set the temperature to 200℃ and the speed to 60r / min.
[0079] (2) Add UHMWPE in several batches within 5 minutes until the torque gradually stabilizes.
[0080] (3) Then add graphite in batches over 5 minutes, and the torque gradually increases.
[0081] (4) After adding graphite, add BN and Pb powder in sequence (add Pb after adding BN, and add them in multiple equal parts).
[0082] (5) After the raw materials are added, continue to knead for 10 minutes. During this stage, the torque will first remain constant and then gradually decrease.
[0083] (6) Stop the internal mixing process and obtain the internally mixed material.
[0084] 2. The hot pressing process is as follows:
[0085] (1) Start the hot press and set the temperature of both the upper and lower plates to 200℃.
[0086] (2) Spread the kneaded material evenly in the mold and place it in the hot press for 5 minutes to plasticize.
[0087] (3) Repeat the pressurization (10MPa) and depressurization (0MPa) exhaust process 5 times to remove gas.
[0088] (4) Hold the pressure at 200℃ and 10MPa for 10 minutes.
[0089] (5) Transfer the mold to the cold press and cold press at 10MPa for 5 minutes to fix the shape. Take out the sample strip to obtain the final product.
[0090] Example 2: Preparation of the thermally conductive nuclear radiation shielding composite material of the present invention
[0091] The raw material formulation of the thermally conductive nuclear radiation shielding composite material of the present invention is shown in Table 3.
[0092] Table 3. Raw material formulation of the thermally conductive nuclear radiation shielding composite material of the present invention
[0093]
[0094]
[0095] The preparation method of the UHMWPE-based thermally conductive nuclear radiation shielding composite material of the present invention is the same as that in Example 1.
[0096] Example 3: Preparation of the thermally conductive nuclear radiation shielding composite material of the present invention
[0097] The raw material formulation of the thermally conductive nuclear radiation shielding composite material of the present invention is shown in Table 4.
[0098] Table 4. Raw material formulation of the thermally conductive nuclear radiation shielding composite material of the present invention
[0099]
[0100] The preparation method of the UHMWPE-based thermally conductive nuclear radiation shielding composite material of this invention consists of two processes: mixing and hot pressing. The composite material is obtained by first mixing and then hot pressing. The specific preparation method is as follows:
[0101] 1. The mixing process is as follows:
[0102] (1) Start the internal mixer, set the temperature to 200℃ and the speed to 60r / min.
[0103] (2) Add UHMWPE in several batches within 5 minutes until the torque gradually stabilizes.
[0104] (3) Add Pb powder in batches within 10 minutes, and the torque gradually increases.
[0105] (4) After adding Pb powder, continue to add BN or graphite, and keep the torque constant.
[0106] (5) After the raw materials are added, continue to knead for 10 minutes. During this stage, the torque will first remain constant and then gradually decrease.
[0107] (6) Stop the internal mixing process and obtain the internally mixed material.
[0108] 2. The hot pressing process is as follows:
[0109] (1) Start the hot press and set the temperature of both the upper and lower plates to 200℃.
[0110] (2) Spread the kneaded material evenly in the mold and place it in the hot press for 5 minutes to plasticize.
[0111] (3) Repeat the pressurization (10MPa) and depressurization (0MPa) exhaust process 5 times to remove gas.
[0112] (4) Hold the pressure at 200℃ and 10MPa for 10 minutes.
[0113] (5) Transfer the mold to the cold press and cold press at 10MPa for 5 minutes to fix the shape. Take out the sample strip to obtain the final product.
[0114] The following specific experimental examples demonstrate the beneficial effects of the present invention.
[0115] The samples used in the test examples were those prepared in Examples 1 to 3.
[0116] Experimental Example 1: Characterization of the Physicochemical Properties of the Thermally Conductive Nuclear Radiation Shielding Composite Material of the Present Invention
[0117] 1. Experimental Methods
[0118] 1.1 Thermal conductivity test
[0119] The thermal conductivity (TC) of the samples was measured using a Hot Disk 2500S instrument manufactured by Hot Disk AB of Sweden. The experiment type was block (Type I), the thermal conductivity probe was model 7577, with a radius of 2 mm, a detection depth of 4 mm, a heating power of 15 mW, and a measurement time of 10 s.
[0120] 1.2 Scanning Electron Microscopy Analysis
[0121] The sample was cut into small strips with notches, approximately 20mm × 5mm × 4mm in size, using a cutting machine. After being frozen in liquid nitrogen for 24 hours, the cross-section was obtained by quenching in liquid nitrogen. The cross-section was then treated with gold sputtering, and the cross-sectional morphology of the material was observed using a scanning electron microscope.
[0122] 1.3 X-ray diffraction analysis
[0123] X-ray diffractometer (Ultima IV, Rigaku, Japan) was used to scan the test samples to determine whether the hot-pressing process would cause BN to orient within the matrix. The scanning range was 2θ = 2–90°. Before testing, the samples were cut into small samples of 10 mm × 10 mm × 4 mm using a cutting machine, and the upper surface (the surface during hot pressing) and the side surface were designated as surface A and surface B, respectively, to investigate the orientation of the filler in different directions.
[0124] 1.4 Mechanical Property Analysis
[0125] The mechanical properties were tested using a universal testing instrument.
[0126] Tensile properties were prepared and tested according to GB / T 1040.2-2022 standard. The specimen dimensions were dumbbell-shaped, with a length × width × thickness of 150 mm × 10 mm × 4 mm. The tensile speed was 5 mm / min, the initial distance between the fixtures was 115 mm, and the gauge length was 50 mm.
[0127] Bending performance was tested and sampled according to GB / T 9341-2008 standard. The sample dimensions were length × width × thickness = 80mm × 10mm × 4mm. The bending speed was 2mm / min, and the gauge length was 64mm.
[0128] 1.5 Density Analysis
[0129] The density of the composite material was tested using the MDJ-300A multi-functional electronic densitometer from Shanghai Lichen Bangxi Instrument Technology Co., Ltd., to verify the material's lightweight properties and provide relevant data for Geant4 simulation calculations.
[0130] 2. Experimental Results
[0131] 2.1 Test results of the sample prepared in Example 1
[0132] 2.1.1 Thermal conductivity analysis
[0133] The thermal conductivity results of samples BN30C10, BN30C20, BN30C10Pb20 and BN30C20Pb20 prepared in Example 1 are as follows: Figure 1 As shown in (a). By Figure 1(a) shows that the thermal conductivity of pure UHMWPE is 0.47 W / mK. The thermal conductivity of the composite material prepared after adding BN and C is significantly improved, and the thermal conductivity of the composite material increases with increasing C content. Compared with the system without Pb (Pb0), the thermal conductivity of the composite material after adding 20 wt% Pb (Pb20) increases from 2.25 (BN30C10) and 3.81 (BN30C20) to 4.18 (BN30C10Pb20) and 6.20 W / mK (BN30C20Pb20), respectively, representing increases of 85.78% and 62.73%. This indicates that the addition of Pb can significantly improve the thermal conductivity of the composite material. At this point, the volume fraction of Pb is only 3%, meaning that adding 3% Pb powder can increase the thermal conductivity of the material by 85.78%, a significant improvement.
[0134] The contribution of a unit mass of filler to thermal conductivity is calculated using the following formula:
[0135] ξ = [ ( λ - λ0 ) / λ0 ] / ω (1)
[0136] Where λ and λ0 represent the thermal conductivity of UHMWPE-based thermally conductive composite material and pure UHMWPE, respectively. ω represents the total mass fraction of the thermally conductive filler.
[0137] Figure 1 (b) The figure shows the contribution of filler per unit mass to thermal conductivity. Comparing BN30C10 and BN30C20, it can be seen that the contribution of filler per unit mass to thermal conductivity increases, and the contribution of filler per unit mass to thermal conductivity also increases after the addition of Pb.
[0138] 2.1.2 Mechanical Property Analysis
[0139] The mechanical property test results of pure UHMWPE and the samples BN30C10, BN30C20, BN30C10Pb20 and BN30C20Pb20 prepared in Example 1 are as follows: Figure 1 As shown in (c) and 1(d). By Figure 1 As shown in (c) and 1(d), compared with pure UHMWPE, the tensile strength and flexural strength of each UHMWPE-based composite material are improved. In particular, the addition of 20wt% Pb significantly improves the tensile strength and flexural strength of the composite material. The tensile strength of BN30C10Pb20 and BN30C20Pb20 are increased by 27.74% and 25.39% respectively compared with BN30C10 and BN30C20 without Pb, and the flexural strength is increased by 41.37% and 29.73% respectively, showing significant improvement in mechanical properties.
[0140] 2.1.3 Scanning Electron Microscopy Analysis
[0141] SEM images of samples BN30C10Pb20 and BN30C20Pb20 prepared in Example 1 are shown below. Figure 2 As shown. By Figure 2 It is evident that the flake-shaped BN and graphite fillers are oriented within the matrix, and the different sizes of BN and graphite contribute to the formation of a thermally conductive network, fully leveraging the excellent thermal conductivity of both BN and graphite. Furthermore, electron microscopy reveals that Pb exists as elliptical particles within the matrix. The presence of Pb allows for better overlap of the flake-shaped fillers, forming a filler network structure within the composite material together with the flake-shaped BN and C. This filler network structure contributes to improving the thermal conductivity of the composite material. Finally, when the material is under stress, the filler network structure effectively transfers stress, allowing more of the matrix to bear the load. This explains why the addition of Pb increases tensile and flexural strength.
[0142] 2.1.4 XRD Analysis
[0143] Figure 3 The XRD patterns of fillers BN and C are shown. Figure 5 The XRD patterns of the A and B sides of samples BN30C10Pb20 and BN30C20Pb20 prepared in Example 1 are shown in Table 5. The corresponding XRD peak values are also shown in Table 5.
[0144] Table 5. XRD Peak Analysis
[0145]
[0146] XRD analysis was performed on the top surface (A side) and side surface (B side) of the sample. Based on the survey, the I of XRD... 002 / I 100 It can characterize the orientation direction and degree of the filler. It can be seen that, whether it is BN30C10Pb20 or BN30C20Pb20, the I-axis of its A-side... 002 / I 100 All are far higher than the I on side B. 002 / I 100 This indicates that the orientation of its sheet-like filler is mainly parallel to the sample surface. However, with the increase of graphite content, I... 002 / I 100 The decrease indicates that excessive filler content disrupts the original orientation state, resulting in a decrease in the degree of orientation.
[0147] 2.2 Test results of samples prepared in Examples 2 and 3
[0148] 2.2.1 Analysis of thermal conductivity and mechanical properties
[0149] 2.2.1.1 Analysis of the thermal conductivity and mechanical properties of the sample prepared in Example 2
[0150] Figure 6 The results of thermal conductivity and mechanical property analysis of the sample prepared in Example 2 are presented. Figure 6 The thermal conductivity results in (a) and (b) show that the thermal conductivity of pure UHMWPE is 0.47 W / mK. The thermal conductivity of the composite material gradually increases with increasing filler content (whether BN or graphite). Specifically, the thermal conductivity of the BN20C20Pb20 system is 4.19 W / mK, with a total filler integral of 33.18%. The thermal conductivity of the composite material further increases with increasing BN content.
[0151] according to Figure 6 The mechanical property results in (c) and 6(d) show that the tensile and flexural strengths of the composite material gradually increase with the increase of filler content (whether BN or graphite). Specifically, the tensile and flexural strengths of the BN20C20Pb20 system are 24.77 MPa and 39.11 MPa, respectively. With increasing BN content, the tensile and flexural strengths of the composite material further improve.
[0152] In summary, BN30C20Pb20 has a thermal conductivity of 6.20 W / mK and tensile and flexural strengths of 27.80 and 49.62 MPa, respectively, making it the optimal formulation.
[0153] 2.2.1.2 Analysis of the thermal conductivity and mechanical properties of the sample prepared in Example 3
[0154] Figure 7 The results of thermal conductivity and mechanical property analysis of the sample prepared in Example 3 are presented. Figure 7 The thermal conductivity results in (a) and 7(b) show that the thermal conductivity of pure UHMWPE is 0.47 W / mK. Adding 80 wt% lead powder improves the thermal conductivity of the composite material to 0.87 W / mK. Furthermore, adding C or BN to the composite material with lead powder significantly improves the thermal conductivity. The thermal conductivity of the Pb80C5 system is 3.29 W / mK, which is 278.16% higher than that of the Pb80 system (0.87 W / mK). At this point, the graphite volume fraction is only 9.99%, and the total filler volume fraction is 38.17%. When 5 wt% BN or graphite is added, the volume fractions are 8.83% and 9.99%, respectively, but the thermal conductivity of Pb80C5 is 42.42% higher than that of Pb80BN5. This indicates that adding graphite provides better thermal conductivity than adding BN. However, compared with BN20C20Pb20 and BN30C10Pb20, Pb80C5 exhibits significantly worse thermal conductivity despite having a higher overall filler integral. This suggests that the combined use of BN and C in the latter can achieve a synergistic effect and better thermal conductivity.
[0155] according to Figure 7 The mechanical property results in (c) and 7(d) show that the mechanical strength of the material is not high when it contains only 80 wt% Pb; the tensile and flexural strengths of the composite material are significantly improved after adding 5 wt% graphite or BN. Specifically, the tensile strengths of Pb80C5 and Pb80BN5 are 24.17 and 24.56 MPa, respectively, and their flexural strengths are 36.33 and 35.00 MPa, respectively. Their tensile strengths are 18.48% and 20.49% higher than that of Pb80 (20.40 MPa), respectively, and their flexural strengths are 35.56% and 30.59% higher than that of Pb80 (26.8 MPa), respectively.
[0156] 2.2.2 SEM Analysis
[0157] Figure 8 SEM images of sample BN20C20Pb20 prepared in Example 2, and samples Pb80, Pb80C5, and Pb80BN5 prepared in Example 3. Figure 8 Analysis:
[0158] In terms of thermal conductivity: the BN20C20Pb20 system shows synergistic thermal conductivity between the lamellar and spherical fillers, with a clear thermal conductivity network. In contrast, Pb80 only contains spherical Pb particles, making it difficult for them to overlap and form a thermal conductivity network. However, with the addition of 5wt% C or BN, a small amount of lamellar filler can connect a large number of spherical particles, creating thermal conductivity pathways and resulting in a rapid increase in thermal conductivity.
[0159] In terms of mechanical properties: the synergistic effect between the flake-like fillers graphite and BN and the granular Pb allows the force at the stress point to be transmitted through the filler network, and enables more molecular chains to bear the force, thus improving the mechanical strength. In Pb80, however, the network is not formed, and only the molecular chains at the stress point bear the force, resulting in lower strength; but after adding 5 wt% C or BN, the network is formed, and the stress transmission is effectively improved, thus enhancing the mechanical strength.
[0160] Figure 9 Mapping analysis results for sample BN20C20Pb20 prepared in Example 2 and sample Pb80BN5 prepared in Example 3. Green represents Pb, and blue represents N, effectively proving that the spherical and plate-like particles are Pb and BN respectively, which can assist SEM analysis in explaining the formation of the thermally conductive network. In BN20C20Pb20, the surface of Pb particles resembles a multilayer structure, and a similar structure can also be seen on the surface of Pb80. Combined with mapping analysis, the spherical particles are Pb, and the wrinkled structure on their surface is likely due to surface damage of the Pb particles during processing.
[0161] Based on the above analysis, the following conclusions are drawn:
[0162] (1) Whether a thermally conductive network or a shielding network is constructed first, a good filler network can be formed between the sheet-like BN and the spherical Pb, constructing a complete thermally conductive path, thereby effectively improving the thermal conductivity of the composite material.
[0163] (2) The presence of filler network greatly improves the tensile and flexural properties of composite materials.
[0164] (3) Combining Examples 1, 2 and 3, the BN30C20Pb20 sample exhibits excellent performance and is the optimal sample.
[0165] 2.2.3 Density Test Data
[0166] The density of the above samples was tested using a densitometer. Each sample was tested three times, and the average was taken as the final density of the material. The results are shown in Table 6. As can be seen from Table 6, the density of the composite material with a Pb mass percentage of 20 wt% is significantly lower than that of the composite material with a Pb mass percentage of 80 wt%, which better meets the requirement of lightweight material.
[0167] Table 6. Density Test
[0168]
[0169] Test Example 2: Nuclear Radiation Shielding Performance Test
[0170] 1. Geant4 data blocking
[0171] Geant4 (Geometry And Tracking) is a Monte Carlo simulation software package developed by CERN using C++ object-oriented technology. It is used to simulate the physical processes of particle transport in matter. Compared to commercial software such as MCNP and EGS, its main advantage is that its source code is completely open, allowing users to modify and extend the Geant4 program according to their specific needs.
[0172] In this experimental example, Geant4 was used to simulate the composite material prepared in the example to predict the neutron penetration performance, linear attenuation coefficient, and mass attenuation coefficient of the material, and to evaluate the neutron shielding performance of the material.
[0173] 1.1 Geant4 Simulation Conditions
[0174] Material types: BN10C10Pb20, BN20C10Pb20, BN30C10Pb20; BN10C20Pb20, BN20C20Pb20, BN30C20Pb20; Pb80, Pb80BN5, Pb80C5.
[0175] Material thickness settings: 2, 4, 6, 8, 10 mm.
[0176] The emitted particles are neutrons, numbering 100,000, with an energy of 5 eV.
[0177] The penetration coefficient I / I0 of the material is calculated by using the number of particles before and after the material is incident by the detector, and its linear attenuation coefficient and mass attenuation coefficient are calculated by the following formula.
[0178] I = I0 e (-μ·d) (2)
[0179] μ m = μ / ρ (3)
[0180] In the formula, I is the penetration intensity of the material; I0 is the incident intensity; d is the thickness of the material; μ is the linear attenuation coefficient; μ m ρ is the mass decay coefficient; ρ is the density of the material.
[0181] 1.2 Summary of Geant4 simulation data
[0182] The Geant4 simulation data is summarized in Tables 7-16. The Geant4 simulation shielding results are as follows: Figure 10 As shown.
[0183] Table 7. Geant4 simulation data for UHMWPE
[0184]
[0185] Table 8. Geant4 simulation data for BN10C10Pb20
[0186]
[0187] Table 9. Geant4 simulation data for BN20C10Pb20
[0188]
[0189] Table 10. Geant4 simulation data for BN30C10Pb20
[0190]
[0191]
[0192] Table 11. Geant4 simulation data for BN10C20Pb20
[0193]
[0194] Table 12. Geant4 simulation data for BN20C20Pb20
[0195]
[0196] Table 13. Geant4 simulation data for BN30C20Pb20
[0197]
[0198] Table 14. Geant4 simulation data for Pb80
[0199]
[0200]
[0201] Table 15. Geant4 simulation data for Pb80BN5
[0202]
[0203] Table 16. Geant4 simulation data for Pb80C5
[0204]
[0205] from Figure 10 As can be seen from (a) to 10(c), the penetration coefficient of the composite material gradually decreases while the linear attenuation coefficient and mass attenuation coefficient gradually increase with increasing material thickness. This is because the increased thickness increases the probability of collisions between neutrons and atoms, thus increasing the likelihood of scattering. Increasing the thickness of the shielding material can improve shielding effectiveness, as neutrons undergo multiple scattering and absorption processes when passing through a thicker material layer. Each scattering and absorption event weakens the energy and intensity of the radiation, thereby enhancing the shielding effect.
[0206] Furthermore, the neutron transmittance gradually decreases with increasing BN content, because B has a strong effect on neutron absorption. The BN30C10Pb20 system has a transmittance of only 25.69% at a thickness of 10 mm, with a linear attenuation coefficient of 1.36 cm⁻¹. -1 The mass decay coefficient is 0.84 cm. 2 / g.
[0207] exist Figure 10 In (d) to 10(f), the content of C increased to 20%, and its I / I0, μ, μ m The trend is similar to the previous group, both showing good shielding effects. Among them, the BN30C20Pb20 system has a transmittance of only 24.78% at a thickness of 10mm, and a linear attenuation coefficient of 1.40cm. -1The mass decay coefficient is 0.77 cm. 2 / g. Compared to BN30C10Pb20, the transmittance is lower, indicating that increasing the C content is beneficial to improving the neutron shielding performance of the material. However, its mass decay coefficient decreases, which may be because although graphite has certain shielding properties, the improvement in shielding effect is offset by the increased mass.
[0208] The BN30C20Pb20 system exhibited good shielding performance at a thickness of 10 mm, with a transmittance of 24.77% and a linear attenuation coefficient of 1.40 cm⁻¹. -1 The mass decay coefficient is 0.77 cm. 2 / g is a thermally conductive shielding material with good neutron shielding effect.
[0209] exist Figure 10 From (g) to 10(i), it can be seen that Pb80BN5 has the best neutron shielding effect in the Pb80 system. This is also because the boron element in BN has a good absorption effect on neutrons. At a thickness of 10 mm, the transmittance of the Pb80 system is 78.24%, and the linear attenuation coefficient is 0.25 cm⁻¹. -1 The mass decay coefficient is 0.07 cm. 2 / g; The Pb80C5 system has a transmittance of 78.71% and a linear attenuation coefficient of 0.24cm. -1 The mass decay coefficient is 0.06 cm. 2 / g; while the Pb80BN5 system has a transmittance of only 46.46% and a linear attenuation coefficient of 0.77cm. -1 The mass decay coefficient is 0.19 cm. 2 / g. The results show that Pb has no significant shielding effect on neutrons, and the shielding effect mainly depends on the BN content. C can slightly reduce the neutron transmittance, but the linear attenuation coefficient and mass attenuation coefficient of the composite material decrease slightly after the addition of graphite. Although the Pb80C5 system is somewhat inferior to Pb80BN5 in terms of shielding performance, it has better thermal conductivity and mechanical properties, and is a high thermal conductivity nuclear radiation shielding material with a certain neutron shielding effect.
[0210] Compared with Example 3, the composite materials prepared in Examples 1 and 2 also show that the combined use of BN and C can achieve a synergistic effect in shielding neutron nuclear radiation.
[0211] In summary, this invention provides a thermoplastic thermally conductive nuclear radiation shielding composite material. This composite material achieves excellent thermal conductivity with low filler content, overcoming the problem of generally poor thermal conductivity of polymers (typically less than 1 W / mK), and can be used in high-temperature radiation environments. At the same time, the composite material of this invention has low density, excellent mechanical properties, and good shielding effect against neutron nuclear radiation, and can be used as a high thermal conductivity nuclear radiation shielding composite material. The composite material prepared by this invention has broad application prospects in the field of nuclear radiation protection.
Claims
1. A thermoplastic thermally conductive nuclear radiation shielding composite material, characterized in that: It is made from the following raw materials by weight percentage: polyethylene 30~60%, ceramic-based filler 10~30%, thermally conductive carbon-based filler 10~20%, and shielding filler 20%; The polyethylene is ultra-high molecular weight polyethylene; The ceramic-based filler is boron nitride; The thermally conductive carbon-based filler is graphite; The shielding filler is lead.
2. The thermoplastic thermally conductive nuclear radiation shielding composite material according to claim 1, characterized in that: It is made from the following raw materials by weight percentage: 30-40% ultra-high molecular weight polyethylene, 20-30% boron nitride, 10-20% graphite, and 20% lead.
3. The thermoplastic thermally conductive nuclear radiation shielding composite material according to claim 2, characterized in that: It is made from the following raw materials by weight percentage: 40% ultra-high molecular weight polyethylene, 20% boron nitride, 20% graphite, and 20% lead; Alternatively, it is made from the following raw materials by weight percentage: 40% ultra-high molecular weight polyethylene, 30% boron nitride, 10% graphite, and 20% lead; Alternatively, it is made from the following raw materials by weight percentage: 30% ultra-high molecular weight polyethylene, 30% boron nitride, 20% graphite, and 20% lead.
4. The thermoplastic thermally conductive nuclear radiation shielding composite material according to any one of claims 1 to 3, characterized in that: The ultra-high molecular weight polyethylene has a molecular weight of 2 million to 4 million.
5. A method for preparing the thermoplastic thermally conductive nuclear radiation shielding composite material according to any one of claims 1 to 4, characterized in that: It includes the following steps: The raw materials are weighed according to their mass percentages and prepared by hot pressing, extrusion molding or injection molding.
6. The use of the thermoplastic thermally conductive nuclear radiation shielding composite material according to any one of claims 1 to 4 in the preparation of nuclear radiation shielding materials.
7. The use according to claim 6, characterized in that: The nuclear radiation shielding material is a high thermal conductivity nuclear radiation shielding material used in high-temperature, nuclear power plant, and mobile nuclear equipment nuclear radiation environments.
Citation Information
Patent Citations
Composite shielding material with neutorn-gamma comprehensive shielding effect
CN103183861A
A polyolefin-based insulating composite material of high thermal conductivity and a preparation method thereof
CN103289175A
High-filling composite shielding material for radiation mixing fields and preparation method of high-filling composite shielding material
CN104409124A
Neutron and gamma-ray radiation shielding material
CN1089055A
Polymer-based heat-conducting composite material, and preparation method and application thereof
CN110835432A